Genomic Analysis of Enterococcus spp. Isolated From a Wastewater Treatment Plant and Its Associated Waters in Umgungundlovu District, South Africa - Mbanga, Joshua; Amoako, Daniel G.; Abia, Akebe L. K.; Allam, Mushal; Ismail, Arshad; Essack, Sabiha Y. (Frontiers in Microbiology, 2021)
We investigated the antibiotic resistome, mobilome, virulome, and phylogenomic lineages of Enterococcus spp. obtained from a wastewater treatment plant and its associated waters using whole-genome sequencing (WGS) and bioinformatics tools. The whole genomes of Enterococcus isolates including E. faecalis (n=4), E. faecium (n=5), E. hirae (n=2), and E. durans (n=1) with similar resistance patterns from different sampling sites and time points were sequenced on an Illumina MiSeq machine. Multilocus sequence typing (MLST) analysis revealed two E. faecalis isolates that had a common sequence type ST179; the rest had unique sequence types ST841, and ST300. The E. faecium genomes belonged to 3 sequence types, ST94 (n=2), ST361 (n=2) and ST1096 (n=1). Detected resistance genes included those encoding tetracycline (tet(S), tet(M), tet(L) and macrolides (msr(C), msr(D), erm(B), mef(A) resistance. Antibiotic resistance genes were associated with insertion sequences (IS6, ISL3, IS982), and transposons (Tn3, Tn6000). The tet(M) resistance gene was consistently found associated with a conjugative transposon protein (TcpC). A total of 20 different virulence genes were identified in E. faecalis and E. faecium including those encoding for sex pheromones (cCF10, cOB1, cad, came), adhesion (ace, SrtA, ebpA, ebpC, efaAfs), and cell invasion (hylA, hylB). Several virulence genes were associated with the insertion sequence IS256. No virulence genes were detected in E. hirae and E. durans. Phylogenetic analysis revealed that all Enterococcus spp. isolates were more closely related to animal and environmental isolates than clinical isolates. Enterococcus spp. with a diverse range of resistance and virulence genes as well as associated mobile genetic elements (MGEs) exist in the wastewater environment in South Africa.